Perlindungan Hukum dalam Equity Crowdfunding: Analisis Terhadap Peran Penerbit, Pemodal, Penyelenggara - Khatimah, Husnul (LPPM Universitas Ekasakti Padang, 2024)
Crowdfunding services through stock offerings are one of the investment options in the community where this implementation helps companies that need capital to obtain capital for the development of the company and have more funds for the utilization of company productivity through an intermediary called the implementation of crowdfunding services. Risks in every business implementation must be a concern and issues regarding protection for related parties are an important factor in supporting business continuity for trust. To maintain public trust, the protection of consumers in the financial services sector is regulated, which regulates the protection of investor funds, the organizer who manages investor funds and distributes them to issuers has an important role in equity crowdfunding so that the responsibilities are also heavy, this is regulated in OJK regulations.